109k views
4 votes
-6x + 6y = 6
-6x + 3y=-12

2 Answers

7 votes

Answer:

y= 6

x= 5

Explanation:

i used substitution where you move everything except one variable to the the other side and substitute it into the other equation

User Abhijith Konnayil
by
6.0k points
6 votes

Answer:

(5,6)

Explanation:

-6x+6y=6

-6x + 3y =-12

Multiply the first equation by -1

6x-6y=-6

Add this to the second equation

6x-6y=-6

-6x + 3y =-12

---------------------

-3y = -18

Divide each side by -3

-3y/-3 = -18/-3

y =6

Now we need to find x

6x - 6y = -6

6x -6(6) = -6

6x -36 = -6

Add 36 to each side

6x-36+36 = -6+36

6x = 30

Divide each side by 6

6x/6 = 30/6

x =5

User Mmcfly
by
5.2k points